ANALISIS DAMPAK KASUS JUDI ONLINE TERHADAP KESENJANGAN ANAK MUDA DI DICIKUTRA HIGH LAND - Ageng Saepudin Kanda; Feri Aziz (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract In the current digital era, information technology has a huge impact on all aspects of life, including people's behavior patterns and social interactions. Currently internet network access covers all groups and all levels. One of the impacts of advances in technology and communication today is a very broad form of online gambling, also known as online gambling. Initially there was only technology that allowed online games or games that could be accessed via smartphone connected to the internet. However, over time this has developed into a form of gambling that can bring profits to the players. Therefore, looking at the problem formulation, there is a problem formulation, namely what are the impacts and factors resulting from online gambling and how to prevent it. This research uses a qualitative method with the data collection method in this research involving an interview and observation system. The results of this research show the impact of gambling, namely damage to the brain, which causes stress and depression, as well as symptoms such as emotional stress for no reason, loss of enthusiasm, and lack of enthusiasm to live life due to the impact of prolonged stress. To overcome online gambling addiction, it is recommended not to play online gambling games, delete gambling accounts, and focus on practicing religion Keywords: Gambling, Online, Impact, Technology, Society